Relationship between physical activity patterns and health in Singapore primary school children at entry level - Teo, Elaine Shu Hui. (2013)
Purpose: This study investigated (i) the physical activity levels and patterns of Singapore children at Primary school entry-level, (ii) the association between their physical activity levels and health measures, (iii) the influence of gender on their physical activity behaviors, and (iv) the differences between physical activity behaviors on weekdays and weekend days.